KOMUNIKASI SOSIAL TERHADAP AKSES HUKUM BAGI MASYARAKAT - Yuhandra, Erga; Bachtiar, Beben Muhammad; Andriyani, Yani; Firdaus, M Iqbal Roihanul (LPPM Univeristas Siliwangi, 2025)
Social communication is a vital instrument in expanding legal access for communities, particularly for vulnerable groups that frequently encounter structural and cultural barriers. The main challenges identified include limited legal literacy, insufficient dissemination of information, and the gap between legal language and everyday community language. These issues result in low legal awareness and restricted capacity of individuals to defend their rights. This study employs a qualitative approach through in-depth interviews and participatory observation of communities in both urban and rural areas. It examines the role of social communication in bridging these gaps by emphasizing its functions of socialization, education, and public participation. The proposed alternative solutions include strengthening community-based legal communication, utilizing accessible digital media, and fostering collaboration among state institutions, civil society organizations, and local leaders in disseminating legal information. Therefore, social communication serves not only as a medium of message exchange but also as a strategic instrument for achieving inclusive justice.